2016
DOI: 10.3732/ajb.1600026
|View full text |Cite
|
Sign up to set email alerts
|

Moss antheridia are desiccation tolerant: Rehydration dynamics influence sperm release in Bryum argenteum

Abstract: For the first time, moss antheridia are shown to be fully desiccation tolerant at a functional level, capable of releasing fully functional sperm following a slow drying event provided the antheridia are allowed to rehydrate at least 3 h before immersion in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The procedure to observe bryophyte sperms described in literature is to submerge the antheridia in water, wait for the release of white sperm masses, collect these with a micropipette, and observe them in a microscope counting chamber [23, 24, 26]. Attempting to use these methods with P. patens , we failed to observe the release of white sperm masses under a dissecting microscope (shown e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure to observe bryophyte sperms described in literature is to submerge the antheridia in water, wait for the release of white sperm masses, collect these with a micropipette, and observe them in a microscope counting chamber [23, 24, 26]. Attempting to use these methods with P. patens , we failed to observe the release of white sperm masses under a dissecting microscope (shown e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Attempting to use these methods with P. patens , we failed to observe the release of white sperm masses under a dissecting microscope (shown e.g. in [24]) or motile spermatozoids. Paolillo [21] describes observing the release of sperms of Funaria hygrometrica (like P. patens a Funariaceae species) as “delicate and tedious” in comparison to e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sheer quantities of sperm produced and their release over several months ensure that at least one flooding event will result in sporophyte production. Highly effective spermatozoid transport both within individual plants and between them, plus recent demonstrations of sperm and antheridial desiccation tolerance (Abel, ; Shortlidge et al, ; Stark et al, ; Döbbeler, ) must also make further contributions to the very high success rate of fertilization. The internalized external water‐conducting system in Marchantia , comprising pegged rhizoids inside the ventral scales and carpocephala grooves, with flow rates of several cm/h (Duckett et al, ) is in fact far more effective at maintaining water balance than hydroids in polytrichalean mosses (Duckett & Ligrone, ).…”
Section: Discussionmentioning
confidence: 99%
“…Schofield (1971) discussed how low levels of free water along with the generally isolated patches of mostly dioicous (>60%) species (which may form single sex colonies) may limit sexual reproduction in the Arctic. Recent studies have shown, however, that sexual reproduction can occur in environments with only short-term availability of free water, as sperm cells and antheridia can withstand dehydration (Shortlidge et al 2012;Stark et al 2016). Monoicous acrocarpous taxa tend to reproduce sexually regularly (Schofield 1971;Longton 1988), but phenological data are lacking or incomplete for most taxa.…”
Section: Long-distance Dispersalmentioning
confidence: 99%